Prevalence of Metabolic Disease among Adults in Indonesia: A Cross-Sectional Population-Based Survey - Fatimah, Meliya Husnatul; Ismail, Aem (Journal of Health Economic and Policy Research (JHEPR), 2024)
Introduction: Metabolic diseases were the leading cause of morbidity and mortality in the world. the World Health Organization, the effective delivery of public health messages has become increasingly complicated due to CKD as a complication of cardiovascular disease and diabetes. Studies have prevalence of metabolic disease among adults in Indonesia. These study aims were to determine the prevalence of kidney, cardiovascular, diabetes. Method: This study uses a cross-sectional study design used from Indonesia Family Life Survey Wave 5 (IFLS-5) organized by Rand Corporation conducted in 2014-2015. A statistical analysis is a descriptive observational study. The total number of respondents un this study was 27,718. Result: Respondents with adult criteria in Indonesia were 52.67% women aged 38.20(±13.64), 78.48% married, 32.94%elementary, and 59.89% urban residents. The prevalence of chronic kidney disease among adults in Indonesia was 1.43% (95% CI: 00.01 – 0.02). The prevalence of cardiovascular disease among adults in Indonesia was 1.64% (95% CI: 00.01 – 0.02). The prevalence of diabetes among adults in Indonesia was 2.33% (95% CI: 00.02 – 0.03). Conclusion: The prevalence of chronic kidney disease, cardiovascular disease, and diabetes in Indonesia is strongly by age and show a relationship between sufferers of these three diseases.